STRATEGI PENGEMBANGAN URBAN HERITAGE TOURISM KOTA CIREBON, JAWA BARAT - Jayanti, Theresia Budi (Jurnal Koridor, 2017)
Tourism potential of a city can be developed through the city’s historical heritage. The history of Cirebon began around the 15th century, a small village in the Java Sea Coast named Muara Jati and its develop into the kingdom with a King named Walangsungsang (Cakrabumi). In the years 1529-1945, the Kingdom of Cirebon developed into four (4) Royal Palaces, namely: Karatons Kasepuhan, Royal Palaces Kanoman, Royal Palaces Kacirebonan and the Royal Palaces Kaprabonan. It’s cause Cirebon City has potential historical sights. Seeing the potential access of existing and historical value, Cirebon City tourism can be developed through the concept of urban heritage tourism. This study aims to discover the potential and strategies for developing the urban heritage tourism concept in Cirebon City. The research method used descriptive qualitative approach. Primary data obtained by field observations and documentation. Secondary data were obtained through, journals, books and the Internet data that is relevant. Then analysis of urban heritage tourism development strategy through a SWOT analysis. The findings are: access, historic building, cultural daily life, community and government is crucial in the development of urban heritage tourism Cirebon City.